2022
DOI: 10.3390/s22082853
|View full text |Cite
|
Sign up to set email alerts
|

Scorepochs: A Computer-Aided Scoring Tool for Resting-State M/EEG Epochs

Abstract: M/EEG resting-state analysis often requires the definition of the epoch length and the criteria in order to select which epochs to include in the subsequent steps. However, the effects of epoch selection remain scarcely investigated and the procedure used to (visually) inspect, label, and remove bad epochs is often not documented, thereby hindering the reproducibility of the reported results. In this study, we present Scorepochs, a simple and freely available tool for the automatic scoring of resting-state M/E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There are a large number of data cleaning pipelines available, however, it has been reported that several of these techniques can introduce artifacts themselves [4], and it can be difficult to know which technique to use first, or which method is suitable to apply to one's data depending on the type of artifact present. For example, state-of-the-art techniques such as Independent Component Analysis (ICA) rely on multiple EEG channels to separate a multivariate signal into independent components [5], in addition to requiring in depth knowledge of EEG activity that is typically considered an artifact [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are a large number of data cleaning pipelines available, however, it has been reported that several of these techniques can introduce artifacts themselves [4], and it can be difficult to know which technique to use first, or which method is suitable to apply to one's data depending on the type of artifact present. For example, state-of-the-art techniques such as Independent Component Analysis (ICA) rely on multiple EEG channels to separate a multivariate signal into independent components [5], in addition to requiring in depth knowledge of EEG activity that is typically considered an artifact [6].…”
Section: Introductionmentioning
confidence: 99%